Persepsi Remaja tentang Pernikahan Usia Anak - Pintam Ayu Yastirin (Universitas STRADA Indonesia, 2019)
Child is someone who is <18 years old. Every child has the right to get protection against sexual and violent crime. In 2017 in Indonesia the population aged 0-17 years was 79,625 with a ratio of more men (40,452) than women (39,173 people). Of these, not all children in Indonesia have obtained their rights properly. Indonesia still has a big task in solving child problems. Various problems that are still faced by Indonesian children include child age marriage, child health and children's education. According to 2013 UNICEF data in KPPA (2018) there are 457,6 thousand women aged 20-24 in Indonesia who are married at the age of <15 years.